Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/8251961
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative and Nitro‐Oxidative Damage in Silver Nanoparticles Cytotoxic Effect against Human Pancreatic Ductal Adenocarcinoma Cells

Abstract: Pancreatic ductal adenocarcinoma is one of the most aggressive human malignancies, where the 5-year survival rate is less than 4% worldwide. Successful treatment of pancreatic cancer is a challenge for today's oncology. Several studies showed that increased levels of oxidative stress may cause cancer cells damage and death. Therefore, we hypothesized that oxidative as well as nitro-oxidative stress is one of the mechanisms inducing pancreatic cancer programmed cell death. We decided to use silver nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 84 publications
(108 reference statements)
3
35
0
Order By: Relevance
“…However, a number of studies have shown that SNPs induced reactive oxygen species production, resulting in apoptosis. 65,66 The current results showed that D-SNPs induced the greatest toxic effects against HepG2 cells. The higher sensitivity of HepG2 cells to D-SNPs may have been due to charge and the type of biomolecules surrounding D-SNPs.…”
Section: Resultsmentioning
confidence: 59%
“…However, a number of studies have shown that SNPs induced reactive oxygen species production, resulting in apoptosis. 65,66 The current results showed that D-SNPs induced the greatest toxic effects against HepG2 cells. The higher sensitivity of HepG2 cells to D-SNPs may have been due to charge and the type of biomolecules surrounding D-SNPs.…”
Section: Resultsmentioning
confidence: 59%
“…Another study also reported that AgNP attenuated the expression of iNOS inhibiting production of nitric oxide in Hep-G2 cells (Zuberek et al, 2017). Although findings of other studies have shown that AgNP can induce expression of iNOS due to increased ROS generation such as in pancreatic cancer and osteoblastic cell lines (Barcinska et al, 2018;Zielinska et al, 2016), this may be as a result of differing cellular responses to AgNP because of the different genetic backgrounds.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 96%
“…The amount of NO was significantly augmented in THP-1 cells incubated with 25, 50, 75, 100, 125, and 150 µg/mL PtNPs to 5, 9, 15, 20, and 25 µM respectively. Silver NPs induce NO in various types of cancer cells including human pancreatic ductal adenocarcinoma and human alveolar basal epithelial cells [39,51]. Platinum NPs similarly induce NO in cancerous cells such as THP-1 and human prostate cancer cells [17,22].…”
Section: Platinum-based Nps Induce Ros Lipid Peroxidation (Lpo) Nitmentioning
confidence: 99%